Differences of articular and extra-articular involvement in polymyalgia rheumatica: A comparison by whole-body FDG-PET/CT. Issue 2 (3rd March 2020) - Kaneko, Koichiro; Suematsu, Eiichi; Miyamura, Tomoya; Ishioka, Hisakazu
Abstract: Objectives: To clarify differences in incidences of articular and extra-articular involvement in patients with polymyalgia rheumatica (PMR) using FDG-PET/CT. Methods: Twenty PMR patients were enrolled in this retrospective study. We compared frequency, degree, and patterns (diffuse or non-diffuse) of abnormal FDG accumulation in the proximal and distal articular structures (PAS, DAS), and extra-articular synovial structures (ESS). Regional analyses were performed for the large joints (shoulder, hip, and knee). Results: The incidences of positive FDG accumulation were significantly higher in the PAS (96.7%) and ESS (91.4%) than in the DAS (31.8%, p < .0001), although, the incidence in the knees (96.2%) was exceptionally high. PAS (2.79 ± 0.61) and ESS (2.52 ± 0.85) had significantly higher visual scores than DAS (0.89 ± 1.33, p < .0001). Shoulder, hip, and knee joints each had a different accumulation pattern. Strong FDG accumulation was frequently observed in the medial-to-subscapular part of the shoulder joints, the lateral part of the hip joints, and the medial part of the knee joints. Conclusion: ESS were found to be the main affected areas in PMR patients as well as PAS. DAS involvement occurred with low frequency except in the knee joints. Each large joint showed a different accumulation pattern and its own characteristically strongly affected areas.